Surface texture modulation via buckling in porous inclined mechanical metamaterials. (February 2022) - Fernandes, Matheus C.; Mhatre, Saurabh; Forte, Antonio E.; Zhao, Bing; Mesa, Olga; Weaver, James C.; Bechthold, Martin; Bertoldi, Katia
Abstract: Porous materials with well-defined periodicity are commonly encountered in biological and synthetic structures and exhibit a wide range of behaviors, ranging from negative Poisson's ratios, to high energy absorption and acoustic damping. Recently, the response of these systems has been shown to be enhanced by mechanical instabilities that lead to sudden and reversible geometric transformations. Although buckling induces planar transformations in most of 2D porous metamaterials, here we describe the emergence of 3D morphologies triggered by mechanical instabilities in an elastomeric block with tilted cylindrical holes. As a proof of concept, we demonstrate that these structures can be leveraged to tune surface properties including friction and light reflection, thus providing a new experimental platform for investigating deformation-dependent dynamics for tribological and optical applications.